1989
DOI: 10.1007/bf00595896
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fever and neutropenia with antibiotics versus antibiotics plus intravenous gammaglobulin in childhood leukemia

Abstract: Thirty-three children with leukemia who had neutropenia and fever were randomized to receive cefataxim and amikacin, versus the same antibiotics plus intravenous gammaglobulin (i.v. IgG). Duration of neutropenia, hospitalization and the interruption of chemotherapy were not different in the two groups; however, duration of fever was significantly shorter in the i.v. IgG group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…К концу 1980-х годов этот метод стал широко распространенным и зарекомендовал себя как один из наиболее эффективных и безопасных [7]. Применение ВВИГ при ИТП послужило поводом к более активному применению данной группы препаратов в гематологии-онкологии и при ТГСК -был выпущен ряд работ, демонстрирующих эффективность у пациентов с нейтропениями и другими осложнениями при остром лимфобластном лейкозе и при ТГСК [8][9]. Так, например, было показано, что профилактическое применение ВВИГ в дозе 0,5 г/кг массы тела пациента значимо снижало риски развития острой реакции «трансплантат против хозяина», интерстициальной пневмонии и других инфекций.…”
Section: томunclassified
“…К концу 1980-х годов этот метод стал широко распространенным и зарекомендовал себя как один из наиболее эффективных и безопасных [7]. Применение ВВИГ при ИТП послужило поводом к более активному применению данной группы препаратов в гематологии-онкологии и при ТГСК -был выпущен ряд работ, демонстрирующих эффективность у пациентов с нейтропениями и другими осложнениями при остром лимфобластном лейкозе и при ТГСК [8][9]. Так, например, было показано, что профилактическое применение ВВИГ в дозе 0,5 г/кг массы тела пациента значимо снижало риски развития острой реакции «трансплантат против хозяина», интерстициальной пневмонии и других инфекций.…”
Section: томunclassified
“…It was proposed to systematically replete patients with intravenous immunoglobulins (IVIG) to limit the risk of infection after allo‐HSCT 7,8 . Different substitution regimens were studied with conflicting results 9‐13 . Meta‐analysis concluded that there was no benefit of a systematic substitution of IVIG on the occurrence of infections, infection‐related mortality, and overall mortality 14 …”
Section: Introductionmentioning
confidence: 99%
“…17 Additionally, IVIG has been used to augment antibiotic treatment in children with leukemia and fever and neutropenia. Sumer et al 18 randomly assigned 33 children to receive either antibiotics with IVIG or antibiotics without IVIG. They found that the duration of fever in the IVIG group was significantly shorter, although the duration of interruption of chemotherapy and length of hospitalization and neutropenia were not different.…”
Section: Introductionmentioning
confidence: 99%